2009
DOI: 10.1016/j.jrp.2009.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Temperament in middle childhood: A behavioral genetic analysis of fathers’ and mothers’ reports

Abstract: The genetic and environmental sources of variance in mothers’ and fathers’ ratings of child temperament in middle childhood were estimated and compared. Parents of 88 MZ twin pairs and 109 same-sex DZ twin pairs completed a temperament questionnaire. For Effortful Control, significant genetic and environmental effects were indicated across mothers’ and fathers’ ratings, but parent differences were found for the Negative Affectivity factor. When present, sibling contrast effects were not consistent for mothers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
37
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 34 publications
10
37
0
Order By: Relevance
“…Subsequent longitudinal analyses of this sample showed that the temporal stability of individual differences was accounted for by stable genetic influences (Deater-Deckard & Wang, 2012). These results are consistent with the literature showing age-based increases in heritabilities for EC and EF (Mullineaux et al, 2009), resulting in very substantial heritability and genetic overlap between sub-components of EF by early adulthood along with distinct genetic variances for subdomains of EF (Miyake & Friedman, 2012). …”
Section: Gene-environment Interplaysupporting
confidence: 92%
“…Subsequent longitudinal analyses of this sample showed that the temporal stability of individual differences was accounted for by stable genetic influences (Deater-Deckard & Wang, 2012). These results are consistent with the literature showing age-based increases in heritabilities for EC and EF (Mullineaux et al, 2009), resulting in very substantial heritability and genetic overlap between sub-components of EF by early adulthood along with distinct genetic variances for subdomains of EF (Miyake & Friedman, 2012). …”
Section: Gene-environment Interplaysupporting
confidence: 92%
“…The individual facets of shyness and soothability were reverse scored for inclusion in the factor composites, so that higher values represented higher Surgency and Negative Affectivity respectively. In previous analyses, we confirmed the measurement structure of the CBQ-SF and found the reliability (i.e., alpha coefficients) to be satisfactory (Mullineaux, Deater-Deckard, Petrill, Thompson, & DeThorne, 2009). Despite concerns regarding bias in the use of parent reporting, such measures are able to reflect children’s behaviors across time and context, thereby offering a fuller view of development than a single observational or standardized assessment.…”
Section: Methodssupporting
confidence: 74%
“…Means ranged from 5.00 to 5.70 ( SD s from .56 to .88) for Effortful Control and its individual facets, from 3.52 to 4.67 ( SD s from .70 to 1.20) for Surgency/Extraversion and its facets, and from 3.58 to 4.25 ( SD s from .66 to 1.10) for Negative Affectivity and its facets. As reported elsewhere (Mullineaux et al, 2009), the correlations between the three temperament factors on the CBQ-SF were generally modest in magnitude.…”
Section: Resultssupporting
confidence: 60%
“…In terms of behavioral SR, studies of effortful control among children and adolescents point to evidence, across informants, of moderate levels (typically 40 to 60% range) of heritable and nonshared environmental variance and negligible shared environmental variance (Goldsmith, Buss, & Lemery, 1997; Lemery-Chalfant, Doelger, & Goldsmith, 2008; Mullineaux, Deater-Deckard, Petrill, Thompson, & DeThorne, 2009; see Yamagata et al, 2005 for similar findings in adults). Similar results have been obtained for children’s self-control (Wright & Beaver, 2005) with evidence accruing for assortative mating and heritable intergenerational transmission from parent-offspring designs (Boutwell & Beaver, 2010).…”
Section: Genetic Influencesmentioning
confidence: 99%